Expanding confidence in network simulations. - Heidemann, J. (IEEE Network : the magazine of global information exchange)
Networking engineers increasingly depend on simulation to design and deploy complex, heterogeneous networks. Similarly, networking researchers increasingly depend on simulation to investigate the behavior and performance of new protocol designs. Despite such widespread use of simulation, today there exists little common understanding of the degree of validation required for various applications of simulation. Further, only limited knowledge exists regarding the effectiveness of known validation techniques. To investigate these issues, in May 1999 DARPA and NIST organized a workshop on Network Simulation Validation. This article reports on discussions and consensus about issues that arose at the workshop. We describe best current practices for validating simulations and for validating TCP models across various simulation environments. We also discuss interactions between scale and model validation and future challenges for the community